1999
DOI: 10.1021/es9810843
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Light-Duty Motor Vehicle Exhaust Particulate Matter in the Denver, Colorado Area

Abstract: A study to characterize particulate matter emissions from 195 in-use gasoline and diesel passenger vehicles was conducted during the summer of 1996 and the winter of 1997 in the Denver, Colorado region. Vehicles were tested as received on chassis dynamometers using the Federal Test Procedure (FTP) Urban Dynamometer Driving Schedule (UDDS). Both PM-10 and regulated emissions were measured for each phase of the UDDS. Approximately 88% of the PM-10 collected was carbonaceous material, of which the average organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
116
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(137 citation statements)
references
References 15 publications
21
116
0
Order By: Relevance
“…Due to the close proximity of the site to the highway and the high volumes of diesel engine traffic (>20,000 per day), this factor is the highest contributor to EC levels (48%), and is likely strongly influenced (indeed, possibly dominated) by diesel engine emissions. The abundant species in this factor are EC, OC, S, Ca, Fe, Si, Al, Ti, Mn, and these are among the typically measured species in vehicular emissions such as Mg, Al, Si, P, S, Cl, Ca, Fe, Cu, Zn, Br, and Pb as reported by Gillies and Gertler (2000) and Cadle et al (1999). The ratio of EC to OC for this factor was 0.43 which is much higher than typically reported for gasoline engine emissions.…”
Section: Unmix Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Due to the close proximity of the site to the highway and the high volumes of diesel engine traffic (>20,000 per day), this factor is the highest contributor to EC levels (48%), and is likely strongly influenced (indeed, possibly dominated) by diesel engine emissions. The abundant species in this factor are EC, OC, S, Ca, Fe, Si, Al, Ti, Mn, and these are among the typically measured species in vehicular emissions such as Mg, Al, Si, P, S, Cl, Ca, Fe, Cu, Zn, Br, and Pb as reported by Gillies and Gertler (2000) and Cadle et al (1999). The ratio of EC to OC for this factor was 0.43 which is much higher than typically reported for gasoline engine emissions.…”
Section: Unmix Resultsmentioning
confidence: 83%
“…There are several studies that have also indicated the cofounding effects of anthropogenic aerosols (such as industrial emissions, traffic exhausts) and naturally occurring bioaerosols in respiratory disorders (Nel et al, 1998;Takenaka et al, 1995). Emissions from traffic-related sources in urban areas have been examined by several researchers (Cadle et al, 1999;Gillies and Gertler, 2000;HEI, 2002;Schauer et al,1996;Shi et al, 1999). A large cohort epidemiological study is underway in the Greater Cincinnati area to examine the adjuvant role of traffic related and naturally occurring aerosols on enhancing the onset of allergic sensitization in children (LeMasters et al, 2003;Ryan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A series dynamometer tests had proved that the OC/EC ratio was a good indicator to separate diesel vehicle emission from gasoline vehicle emission. When OC/EC was in the range of 0.3-0.9, PM 2.5 was mainly derived from the diesel vehicle, and when OC/EC is larger than 2.0, PM 2.5 was primarily from gasoline car (Cadle et al, 1999;Liu et al, 2012). OC/EC in WZS tunnel ranged from 0.48 to 1.45 with an average value of 0.86.…”
Section: Oc and Ecmentioning
confidence: 99%
“…Currently, only limited measurements of ECOC for diesel engine emissions exist that utilize the NIOSH and IM-PROVE ECOC measurement techniques. A sample of these measurements, which are shown in Table 3, shows that under standardized driving cycle conditions; the EC to TC ratio of diesel particulate matter is in the range of 0.50-0.80 (Hildemann et al, 1991;Lowenthal et al, 1994;Watson et al, 1998;Cadle et al, 1999;Schauer et al, 1999b). Reported measurements of this nature are not sufficient to elucidate the effect of driving cycle, engine type, engine age, and engine fuel on this ratio but they can be expected to be important factors.…”
Section: Atmospheric Sources Of Elemental Carbonmentioning
confidence: 99%
“…e Profile 2, which includes only buses and trucks without particle traps and operated on diesel fuel. powered motor vehicles that have a visible smoke plume, often called smokers, has been measured to be in the range of 0.14 in Denver, Colorado using the IMPROVE ECOC method (Cadle et al, 1999). During the same study, nonsmoking vehicles were measured to have elemental contributions to total particulate carbon of 0.27 and 0.38 for summer and winter tests, respectively.…”
Section: Atmospheric Sources Of Elemental Carbonmentioning
confidence: 99%